(untitled) (Superficies y Vacío, 2022)
We report the growth of In0.145Ga0.855As0.132Sb0.868 layers on GaSb(100) substrates by the liquid phase epitaxy (LPE) technique using the ramp-cooling method. We achieved a near-lattice-matched epitaxial growth with a lattice mismatch of between the quaternary layer and GaSb(100) substrate due to optimal growth parameters. Aberration-corrected scanning transmission electron microscope (AC-STEM) confirmed the high crystalline quality of the quaternary layer and the low lattice mismatch in the heterostructure, without the presence of linear or planar defects. Also, the Secondary Ion Mass Spectrometry (SIMS) technique evidenced a uniform distribution of the atomic elements along the quaternary layer and an abrupt interface between the In0.145Ga0.855As0.132Sb0.868 layer and the GaSb substrate. Plasmon-phonon interactions were observed by Raman spectroscopy indicating that the crystalline quality increases at greater depth in the sample with respect to the surface. The quaternary layer presented a uniform and flat morphology, and luminescence emission attributed to the recombination of bound exciton states at 641 meV. The structural, chemical, and optical properties of the In0.145Ga0.855As0.132Sb0.868 layer demonstrated that it could be auspicious material for infrared range optoelectronic applications. Likewise, the LPE technique successfully shows that it should be used to grow near-lattice-matched heterostructures.